PRIVATE CAPITAL FLOWS AND MACROECONOMIC PERFORMANCE: GROWTH IMPLICATIONS OF SHOCKS FOR SUB-SAHARAN AFRICAN ECONOMIES (2014)
In theory, private capital flows (PCF) strengthen domestic investment for economic growth. In sub-Saharan African (SSA) economies, Foreign Direct Investment per Capita (FDIC), Portfolio Investment per Capita (PIC) and Bank Lending per Capita (BLC) components of PCF grew inversely to Gross Domestic Product per Capita (GDPC). While growth rates of FDIC, PIC and BLC respectively averaged 269.6%, 31.7% and 55.6% in 1981-1990; 42.9%, 36.6% and 28.6% in 1991-2000; 30.7%, -174.7% and 24.2% in 2001-2010; GDPC growth rates were -1.3%, -0.4% and 2.2% over the periods. Previous studies have attributed this problem largely to recipient economies’ structural features, with little attention paid to PCF shocks (sharp fluctuations from the equilibrium path). This study, therefore, investigated the effects of PCF shocks on the macroeconomic performance of selected SSA countries. A stochastic model within a dynamic open-economy framework was developed to evaluate the relationship between shocks to gross inflows of PCF components (FDIC, PIC and BLC) and macroeconomic performance indicators (GDPC, Gross Fixed Capital Formation per Capita (GFCC), and Exchange Rate (ER)). Shocks were measured, using the Structural Vector Autoregressive (SVAR) model, as one-standard deviation of orthogonal structural errors. The Maximum Likelihood estimation technique employed yielded asymptotically efficient estimators which were invariant to the model’s re-parameterisation. The effects of the shocks on GDPC long-term growth were determined using the instrumental variables regression method. Annual data on fourteen SSA countries from 1990 to 2010 were employed, based on data availability. The data were collected from the International Monetary Fund’s International Financial Statistics Yearbook and the World Bank’s Global Development Finance databases. Reliability and robustness of estimators were ascertained using Johansen-Fisher co-integration and SVAR stability tests. Statistical significance was determined at 0.05 level. Shocks to PIC consistently reduced GDPC by $0.33, $0.31 and $0.28 in the first, second and third post-shock years, respectively. Similarly, BLC shocks reduced GDPC by $2.46, $2.54 and $2.49 over the same periods. Both PIC and BLC shocks respectively reduced GDPC long term growth rate by 0.9% and 1.2%. They also led ER to appreciate by 0.02 points and 0.22 points, while GFCC increased by $0.35 and UNIVERSITY OF IBADAN iii $3.52, in that order. However, shocks to FDIC led ER to depreciate by 0.40 points but induced GDPC and GFCC to increase by $0.75 and $0.20, respectively. These results suggested that both real flows (FDI) and financial flows (PIC and BLC) enhanced capital formation. Only real flows effectively induced economic growth, though local currency depreciated because the induced increase in GDPC raised local demand for foreign currency. Financial flows hampered economic growth as the induced ER appreciation constrained GDPC. Shocks to private capital flows significantly influenced macroeconomic performance of sub-Saharan African countries, with foreign direct investment being more growth inducing than private portfolio investment and bank lending. These countries should manage portfolio investment and bank lending flows more effectively to mitigate the negative effects of their shocks. Also, efforts should be intensified to attract foreign direct investment for rapid economic growth.